Amorphous NiCu thin films sputtered on TiO2 nanotube arrays: a noble‐metal free photocatalyst for hydrogen evolution - Pinna, Marco; Wo Weng Wei, Angeline; Spanu, Davide; Will, Johannes; Yokosawa, Tadahiro; Spiecker, Erdmann; Recchia, Sandro; Schmuki, Patrik; Altomare, Marco (ChemCatChem, 2022)
In this work, NiCu co-catalysts on TiO2 are studied for photocatalytic hydrogen evolution. NiCu co-catalyst films are deposited at room temperature by argon plasma sputtering on high aspect-ratio anodic TiO2 nanotubes. To tune the Ni : Cu atomic ratio, alloys of various compositions were used as sputtering targets. Such co-catalyst films are found to be amorphous with small nanocrystalline domains. A series of parameters is investigated, i. e., i) Ni : Cu relative ratio in the sputtered films, ii) NiCu film thickness, and iii) thickness of the TiO2 nanotube layers. The highest photocatalytic activity is obtained with 8 μm long TiO2 nanotubes, sputter-coated with a 10 nm-thick NiCu films with a 1 : 1 Ni : Cu atomic ratio. This photocatalyst reaches a stable hydrogen evolution rate of 186 μL h−1 cm−2, 4.6 and 3 times higher than that of Ni- and Cu-TiO2, respectively, demonstrating a synergistic co-catalytic effect of Ni and Cu in the alloy co-catalyst film.<br